Ex-post assessment of the Kyoto Protocol – quantification of CO2 mitigation impact in both Annex B and non-Annex B countries-. (15th June 2018) - Kuriyama, Akihisa; Abe, Naoya
Highlights: Mitigation effect by the Kyoto Protocol was observed in Annex B non-EIT countries. Small EIT countries had perverse effects on CO2 emission reductions by the Kyoto Protocol during the commitment period. In total, 951 MtCO2 emission reduction was achieved by the Kyoto Protocol, mainly in non-Annex B countries. The results in this paper contribute the discussion of international cooperation mechanisms under the Paris Agreement. Abstract: The Kyoto Protocol implemented the first international top-down mechanisms and provided mitigation incentives for both Annex B and non-Annex B countries. An assessment of the Kyoto Protocol would contribute to the fundamental discussion on designing future mitigation mechanisms under Article 6 of the Paris Agreement, while the use of a top-down approach that includes an emission trading scheme appears important for achieving the 2 °C target. This paper summarizes the existing literature and quantifies the effects of greenhouse gas (GHG) emission reduction impacts from the Kyoto Protocol using the Stochastic Impacts by Regression on Population, Affluence and Technology (STIRPAT) approach for Annex B countries and 'additionality' assessment of Clean Development Mechanisms (CDM) projects for non-Annex B countries. We found that the Kyoto Protocol brought about 951 Mt CO2 e of real emission reductions in all over the world, mainly from implementing non-energy-related GHG emission reduction projects in non-Annex B countries. For the Annex B countries, 76 Mt CO2 e of mitigation occurred during the preparation stage of the first commitment period (2005–2007), but no further effects were observed during the first commitment period (2008–2012). The following important lessons were learned from the implementation of the Kyoto Protocol: (1) insufficient emission caps did not provide any mitigation incentives; rather, they resulted in perverse effects amounting to 12 Mt CO2 e, which increased emissions in certain Annex B countries with economies in transition; and (2) since 42% of energy-related projects in non-Annex B countries were assessed as non-additional projects, more attention needs to be paid to the design of international cooperation mechanisms.